Interventional Effect and Mechanism of Acupuncture at Baihui （GV 20） and Qubin （GB 7） Acupoints on Rats with Acute Cerebral Hemorrhage - CHEN Qiuxin; TANG Yihe; LIU Xiaoying; XU Ning; XU Siyu (康复学报, 2024)
ObjectiveTo investigate the interventional effect of acupuncture at Baihui (GV 20) and Qubin (GB 7) acupoints on the expression of recombinant cluster of differentiation 36 (CD36) and Toll-like receptor 4 (TLR4) in rats with acute cerebral hemorrhage (ICH), and to explore the mechanism of acupuncture treatment for ICH.MethodsA total of 144 male Wistar rats were randomly divided into sham operation group, model group, acupuncture group and inhibitor group, with 36 cases in each group, and then each group was divided into three subgroups at the 1st, 3rd and 7th day, with 12 cases in each subgroup. The stereotaxic autologous blood injection method was used to establish a rat model of ICH. The model group only received ICH model preparation without any treatment. The sham operation group received various operations similar to the model group, but without blood injection. The inhibitor group received an intraperitoneal injection of the TLR4 inhibitor TAK242 at 6 hours after modeling, and the dose was 3 mg/kg, once daily for 5 days. At 12 hours after model establishment, all subgroups of the acupuncture group received penetrative needling at Baihui (GV 20) and Qubin (GV 25) acupoints. The needle was retained at a depth of 20 mm and twisted at a frequency of 100 r/min for three sessions of 2 min each at an interval of 5 min during the 30-min needle retention period. Acupuncture was given once a day and lasted for 1, 3, and 7 days in the three acupuncture subgroups, respectively. At the 1st, 3rd and 7th day after treatment, modified neurological severity score (mNSS) was used to assess neurological function. The volume of hematoma in brain tissue was detected. Western blot was used to detect the protein expression level of CD36 and TLR4 in brain tissue. Immunofluorescence method was used to detect the expression of CD36 and TLR4 in astrocytes.Results(1) mNSS score: compared with the sham operation group at the same time, mNSS score of the model group, the acupuncture group and the inhibitor group at 1, 3, 7 days after treatment increased significantly (P<0.05); compared with the model group at the same time, mNSS score of the acupuncture group and the inhibitor group at 1, 3, 7 days after treatment decreased significantly (P<0.05); compared with the acupuncture group at the same time, mNSS score in the inhibitor group at 1 day after treatment decreased significantly (P<0.05). (2) Hematoma volume: compared with the model group at the same time, hematoma volume in the acupuncture group and the inhibitor group at 3, 7 days after treatment decreased significantly, and hematoma volume in the inhibitor group at 1, 3, 7 days after treatment decreased significantly (P<0.05); compared with the acupuncture group at the same time, hematoma volume in the inhibitor group decreased significantly at 1, 3, 7 days after treatment decreased significantly (P<0.05). (3) Protein expression level of CD36 and TLR4: compared with the sham operation group at the same time, the protein expression level of CD36 and TLR4 in the model group, the acupuncture group and the inhibitor group at 1, 3, 7 days after treatment increased significantly (P<0.05); compared with the model group at the same time, the expression level of CD36 protein in the acupuncture group and the inhibitor group at 1, 3, 7 days after treatment increased significantly (P<0.05), and the expression level of TLR4 protein in the acupuncture group and the inhibitor group at 3, 7 days after treatment decreased significantly (P<0.05); compared with the acupuncture group, the expression level of CD36 protein in the inhibitor group at 1, 3, 7 days after treatment increased significantly, and the expression level of TLR4 protein decreased significantly (P<0.05). (4) Expression level of CD36 and TLR4 in GFAP: there was a small amount of CD36 and TLR4 in the brain tissue of rats in the sham operation group. Compared with the sham operation group at the same time, the expression of CD36 and TLR4 in GFAP in the model group at 1, 3, 7 days after treatment increased significantly (P<0.05); compared with the model group at the same time, the expression of CD36 in GFAP of the inhibitor group and the acupuncture group at 1, 3, 7 days after treatment increased significantly, while the expression of TLR4 in GFAP decreased significantly (P<0.05).ConclusionAcupuncture at Baihui (GV 20) and Qubin (GB 7) acupoints can improve neurological function of rats with acute ICH, alleviate hematoma volume, which may be related to promoting the expression of CD36 protein and inhibiting the expression of TLR4 protein.